Mode of Speech Revolve of Covid 19 in Bahasa Indonesia and Japanese Language in Social Media - Riza Lupi Ardiati; Inu Isnaeni Sidiq; Sigit Sugiarto (IZUMI, 2022)
This research aims to examine mode of speech revolve of Covid 19 in bahasa Indonesia and Japanese language in social media. The revolving of the Covid 19 that has been conveyed on social media by both policy-making officials and the general public has its own style of language that allows the power of speech in various illocutions, related to the efforts made to avoid the Covid 19 virus outbreak. The research method was carried out through qualitative descriptive and using photo-tapping and note-taking techniques. The theory used is, pragmatics refers to Leech (2003), taiguu hyougen from Pon (2004). The results of the study found that the speech revolving Covid 19 was carried out in assertive illocutionary, directive (ordering, pleading and demanding), and expressive (criticizing and praising). Violation of the maxims of quality and quantity is carried out through the ironic power of excessive and understated speech. Face threatening acts in negative face are found in speeches revolving Covid 19 in Indonesian and Japanese. Face threatening acts with positive face are only found in Indonesian. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor